Effectiveness of Using Village Funds during the Covid-19 Pandemic (Case Study in Hiligeho Village, Tanah Masa Subdistrict, Regency South Nias) - Dachi, Theofilus; Yoserizal, Yoserizal; Putera, Roni Ekha (JPSI (Journal of Public Sector Innovations), 2023)
The purpose of this study is to analyze the Effectiveness of the Use of Village Funds during the COVID-19 Pandemic (Case Study in Hiligeho Village, Tanah Masa District, South Nias Regency). The study focuses on the use of Village Funds during the COVID-19 pandemic, which is from 2020 to 2021. This study seeks to find out how the use of the Village Fund during the COVID-19 pandemic by the Hiligeho Village Government and whether the use of the Village Fund during the COVID-19 pandemic has been effective. The theory used is the theory of effectiveness from Makmur, which includes accuracy in timing, accuracy in cost calculations, accuracy in measurement, accuracy in making choices, accuracy in thinking, accuracy in carrying out orders, accuracy in determining goals and targeting accuracy. With descriptive qualitative research methods, data collection techniques used are interviews and documentation. Meanwhile, to ensure the validity of the data, the researcher applied data triangulation. Based on the results of the study, it was found that the use of Village Funds during the COVID-19 pandemic by the Hiligeho Village Government was not yet fully effective. This is known from the implementation of Village Fund priorities, namely the Village Fund for direct cash assistance (BLT), COVID-19 emergency response and Village Cash Intensive Work (PKTD), which are experiencing delays. In addition, several problems in the community empowerment program, such as the distribution of vegetable fertilizer assistance that is not right on target and uneven and the assumption that this program is only for certain groups, cause inequality.